Cardiac sympathectomy and spinal cord stimulation attenuate reflex-mediated norepinephrine release during ischemia preventing ventricular fibrillation - Ardell, Jeffrey L. (JCI Insight, 2019)
The purpose of this study was to define the mechanism by which cardiac neuraxial decentralization or spinal cord stimulation (SCS) reduces ischemia-induced ventricular fibrillation (VF). Direct measurements of norepinephrine (NE) levels in the left ventricular interstitial fluid (ISF) by microdialysis, in response to transient (15-minute) coronary artery occlusion (CAO), were performed in anesthetized canines. Responses were studied in animals with intact neuraxes and were compared with those in which the intrathoracic component of the cardiac neuraxes (stellate ganglia) or the intrinsic cardiac neuronal (ICN) system was surgically delinked from the central nervous system and those with intact neuraxes with preemptive SCS (T1–T3). With intact neuraxes, animals with exaggerated NE release due to CAO were at increased risk for VF. During CAO, there was a 152% increase in NE when the neuraxes were intact compared with 114% following stellate decentralization and 16% following ICN decentralization. During SCS, CAO NE levels increased by 59%. Risk for CAO-induced VF was 38% in controls, 8% following decentralization, and 11% following SCS. These data indicate that ischemia-related afferent neuronal transmission differentially engages central and intrathoracic sympathetic reflexes and amplifies sympathoexcitation. Differences in regional ventricular NE release are associated with increased risk for VF. Surgical decentralization or SCS reduced NE release and VF.